Character Analysis And Service Strategy For Sleeper Bus Consumers On The Malang – Jakarta Route Based On User Perspective - Rahmad Oktantiyo, Abiyyu; Tjendani, Hanie Teki; Sajiyo, Sajiyo (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the character and service strategy for sleeper bus consumers on the Malang-Jakarta route based on the perspective of users. Through a survey approach involving questionnaire instruments, this study integrates the Kano and SERVQUAL methods to identify customer needs and evaluate the gap between expectations and perceptions of service quality. Analysis of user needs characteristics was carried out to understand what attributes are considered important and significantly affect the level of satisfaction in the context of sleeper bus services. The results show that some service attributes fall into the must-be and one-dimensional categories, which are proven to have a strong impact on user satisfaction. Meanwhile, SERVQUAL's analysis identified negative gaps in several service dimensions, especially in terms of reliability and responsiveness. Based on these findings, this study formulated a service improvement strategy that focuses on optimizing priority attributes, improving operational processes, and strengthening comfort and security aspects. This research is expected to contribute to the development of a more responsive and customer-oriented intercity transportation service strategy.